2014
DOI: 10.5901/mjss.2014.v5n14p198
|View full text |Cite
|
Sign up to set email alerts
|

Violence in South African Schools: Perceptions of Communities about a Persistent Problem

Abstract: Multiple incidents of violence in South African

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Studies conducted confirmed that school violence is a global challenge (Burton & Leoschut, 2013;Dunne et al, 2013;UNESCO, 2017;Ngidi, 2018). Similarly, in South Africa, the issue of indiscipline and unsafe school environments is of great concern (UNESCO, 2017;Basic Education Rights Handbook, 2017;Mgijima, 2014). Other studies conducted in South Africa found that school violence results in a loss of teaching and learning because the interruptions require to be attended to (Mkhize et al, 2011;Ncotsa & Shumba, 2013;Netshitangani, 2014;Ngidi, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted confirmed that school violence is a global challenge (Burton & Leoschut, 2013;Dunne et al, 2013;UNESCO, 2017;Ngidi, 2018). Similarly, in South Africa, the issue of indiscipline and unsafe school environments is of great concern (UNESCO, 2017;Basic Education Rights Handbook, 2017;Mgijima, 2014). Other studies conducted in South Africa found that school violence results in a loss of teaching and learning because the interruptions require to be attended to (Mkhize et al, 2011;Ncotsa & Shumba, 2013;Netshitangani, 2014;Ngidi, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whereas an atmosphere of safety is an essential for teaching, learning and educational growth (Department of Education, 2008;Mgijima, 2014), there is a challenge of a high prevalence of violence in South African schools (South African Council of Educators [SACE], 2011;Netshitangani, 2014;Mncube & Steinmann, 2014;Basic Education Rights Handbook, 2017;UNESCO, 2017). Maphosa (2011) concurs that the occurrence of unruly behaviour is rapidly becoming a severe problem for teachers because a dangerous school atmosphere diminishes the quality of education in any school setting.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the need for identification of child maltreatment, there is an urgent need to conduct research to evaluate the effects of current approaches to child protection, as well as the feasibility and effectiveness of evidence-based approaches to the SA context, such as multisystemic therapy and functional family therapy (Celinska, Furrer, & Cheng, 2013;Van der Stouwe, Asscher, Stams, Dekovic, & van der Laan, 2014). Similarly, there is a need to study approaches that address student behavior and school violence, including the training and support for teachers and administrators to implement school and classroom management that relies on proven techniques (e.g., multi-tiered systems of behavioral support; Bradshaw, Reinke, Brown, Bevans, & Leaf, 2008;Horner et al, 2009), rather than the prevalent piecemeal approach to addressing student behavior (see Mgijima, 2014). Further, community-based interventions to address the rampant problems with drugs and gangs in schools and townships are needed, given their association with violence (Mncube & Harber, 2013).…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…It should also be a place where learners can develop healthy relationships with other learners, irrespective of social class, sex, creed, ethnic background, and age (Amedahe & Owusu Banahene, 2007). Both learners and educators are equally at risk, as perpetrators relentlessly pounce on innocent victims (Mgigima, 2014). The negative impact of aggression and violence in schools not only makes the school environment a vulnerable place for educators and learners to do their work and perform other duties peacefully, but also diminishes the quality of education given to learners.…”
Section: Introductionmentioning
confidence: 99%